Fractal growth of ZrO2 nanoparticles induced by synthesis conditions. Issue 43 (17th October 2016) - Stolzenburg, P.; Freytag, A.; Bigall, N. C.; Garnweitner, G.
Abstract : Strong changes in morphology and phase composition of zirconia nanoparticles can be induced by altering the growth conditions during the nonaqueous nanoparticle synthesis. Abstract : Strong changes in morphology and phase composition of zirconia nanoparticles can be induced by altering the growth conditions during nanoparticle synthesis. Here, we demonstrate that fractal ZrO2 nanocrystals showing high specific surface area can be obtained in the nonaqueous synthesis by variation of temperature and precursor concentration. The growth process was studied in detail revealing a size increase from 2.7 to 7 nm as well as a change in the polymorphic composition from tetragonal to monoclinic zirconia. TEM measurements of samples withdrawn over the course of the synthesis showed that particles grow from roundish to dendritic shapes during the phase transformation. In contrast to the common assumption that the phase transition is controlled by thermodynamics, our data shows that the transition is rather governed by kinetics.